Contemporary African Historiographies: Roots, Conflicts, and Trajectories Roots, Conflicts, and Trajectories - Cruz, Reginald D. (Interreligious studies and intercultural theology, 2021)
This paper considers historiographical trends in contemporary African ecclesiastical and civil circles. Given the relative brevity of this essay, it does not pretend to give an exhaustive exposition of the theological trends in this rather vast and multicultural continent. Nonetheless, I hope to paint a satisfactory picture of this landscape, despite the limitations, so that readers could understand the methodological problems, epistemological controversies, and cultural complexities they would encounter through African history.